Human placental mesenchymal stem cells ameliorates premature ovarian insufficiency via modulating gut microbiota and suppressing the inflammation in rats. - Shudan Liu; Ting Wang; Yuanyuan Liu; Yiwei Li; Junbai Ma; Qikuan Hu; Hao Wang; Xiaoxia Zhang (PLoS ONE)
The core objective of this study was to explore the effects and potential mechanism of human placental mesenchymal stem cells (PMSCs) in improving early-onset ovarian dysfunction (POI). Mesenchymal stem cells with multidirectional differentiation ability were isolated from human placenta tissue and a culture system of human PMSCs was constructed for this study. Subsequently, we successfully constructed POI rat models using cisplatin induction. We randomly divided these models into four groups: CON group (blank control), MOD group (POI model), MED group (hormone therapy), and PMSC group (PMSCs therapy). Then, we compared the differences in estrus cycle, ovarian index, ovarian weight, and ovarian histopathological features, as well as hormones and inflammatory factors in rats of diverse groups. The content of lipopolysaccharide (LPS) in plasma was determined by limulus reagent kit. 16S rDNA sequencing was used to evaluate the changes in gut flora composition. Further, we investigated short-chain fatty acids (SCFAs) in the metabolites of rat gut microbiota by gas chromatography-mass spectrometry (GC-MS). As a result, we successfully established an efficient cell culture system of human placental mesenchymal stem cells (PMSCs) in vitro. Then, we evaluated the effects of PMSC intervention on POI rats: Compared to the untreated MOD group, the estrous cycle of rats in the PMSC group gradually became regular, the ovarian weight and ovarian index were significantly increased, and the ovarian tissue structure was improved by showing an increase in the number of follicles and a decrease in the number of atretic follicles. Moreover, PMSC intervention significantly affected plasma sex hormones by a major impact on follicle stimulating hormone (FSH) and Estradiol (E2). In terms of inflammatory factors, PMSC intervention decreased the levels of proinflammatory cytokines including interleukin (IL)-1β, IL-33, IL-6, and tumor necrosis factor (TNF)-α in plasma and ovarian tissue of POI rats. Meanwhile, the expression of anti-inflammatory cytokine IL-10 was increased. In addition, we found that there was ectopic lipopolysaccharide (LPS) in the blood of POI rats, which could be significantly reduced by PMSC intervention. Intestinal microbiota sequencing and analysis showed that after PMSC intervention, the phyla abundances of Firmicutes, Bacteroides, and Proteobacteria showed remarkable differences between the MOD and PMSC groups (P < 0.05). Further genus analysis showed that PMSC treatment had a major influence in gut microbitoa by increasing the abundances of Turicibacter and Desulfovibrio, as well as reducing Alloprevotella, Parabacteroides, Rikenellaceae_RC9_gut_group, and Rikenella. The changes of SCFAs in intestinal microbial metabolites of rats after PMSC intervention were analyzed: caproic acid level was markedly increased, butyric acid showed a decreased trend. Notably, we found a closed and complicated potential correlation among differential microbiota, inflammatory factors and hormones after PMSCs intervention. Collectively, this study have successfully established a suitable cultured PMSCs that can effectively promote the improvement of reproductive function in POI rats and achieve therapeutic effects by regulating the inflammatory response and reshaping the gut intestinal microbiota.